Correlation Between Spirituality Levels and Self-Esteem Among First-Year Students in Health Science Programs - Fitriani, Dwi Rahmah; Sari, Indah Permata; Milkhatun, Milkhatun (Inspirasi Foundation, 2025)
Introduction: Spirituality is one of the important aspects in human life that can affect various psychological aspects, including self-esteem. New students often face adaptation challenges that can affect their self-esteem. Understanding the relationship between the level of spirituality and self-esteem is important to support student well-being, especially in the Health Study Program of the University of Muhammadiyah East Kalimantan. Objective: This study aims to determine the relationship between the level of spirituality and self-esteem of new students in the Health Study Program, Muhammadiyah University of East Kalimantan. Research Method: This study used a cross-sectional design. Measurement of spirituality levels was carried out using the Daily Spiritual Experience Scale (DSES) which has been adapted into Indonesian, while self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES). The research sample of 271 new students was selected using the stratified random sampling technique. Data were analyzed using the Spearman test to determine the relationship between the two variables. Results: The results of the study showed that out of 271 respondents, high spirituality levels were found in 59% of respondents, moderate in 40.2%, and low in 0.7%. Meanwhile, high self-esteem was found in 60.5% of respondents, moderate in 39.1%, and low in 0.4%. Statistical tests showed a p value = 0.000 (<0.05), which means there is a significant relationship between spirituality levels and self-esteem. The Spearman correlation value of 0.878 indicates a positive relationship with a very strong correlation strength. Conclusion: There is a significant positive relationship between the level of spirituality and self-esteem of new students in the Health Study Program, Muhammadiyah University of East Kalimantan. This result indicates that increasing spirituality can contribute to increasing students' self-esteem.